Symplasmic Constriction and Ultrastructural Features of the Sieve Element/Companion Cell Complex in the Transport Phloem of Apoplasmically and Symplasmically Phloem-Loading Species - Kempers, Ronald (American Society of Plant Physiologists, 1998)
The ultrastructural features of the sieve element/companion cell complexes were screened in the stem phloem of two symplasmically loading (squash, [Cucurbita maxima L.] and Lythrum salicaria L.) and two apoplasmically loading (broad bean [Vicia faba L.] and Zinnia elegans L.) species. The distinct ultrastructural differences between the companion cells in the collection phloem of symplasmically and apoplasmically phloem-loading species continue to exist in the transport phloem. Plasmodesmograms of the stem phloem showed a universal symplasmic constriction at the interface between the sieve element/companion cell complex and the phloem parenchyma cells. This contrasts with the huge variation in symplasmic continuity between companion cells and adjoining cells in the collection phloem of symplasmically and apoplasmically loading species. Further, the ultrastructure of the companion cells in the transport phloem faintly reflected the features of the companion cells in the loading zone of the transport phloem. The companion cells of squash contained numerous small vacuoles (or vesicles), and those of L. salicaria contained a limited number of vacuoles. The companion cells of broad bean and Z. elegans possessed small wall protrusions. Implications of the present findings for carbohydrate processing in intact plants are discussed.